Evaluation of safety, efficacy and continuation rates of post-partum intrauterine contraceptive device - Verma, Jayotika; Thakur, Suman; Thakur, Rama; Pathania, Kushla; Thakur, Nitesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postpartum intrauterine contraceptive device (PPIUCD) is a proven, safe, reversible, and long-acting method of contraception. Despite availability, its acceptance remains low. This study aimed to evaluate the safety, efficacy, and continuation rates of PPIUCD in a tertiary care hospital in Himachal Pradesh. Methods: A prospective study was conducted from June 2023 to May 2024 among women >34 weeks gestation attending antenatal outpatient department (OPD), admitted in the labor room, and postpartum ward. PPIUCD insertion was performed either post-placental or intra-caesarean after counselling. Women were followed up at 6 weeks, 12 weeks, and 6 months to assess safety, efficacy and continuation rates. Results: Of 500 women, the acceptance rate was 40%, significantly influenced by antenatal counselling. The main reasons for acceptance were long-term contraception (91.5%), safety (88%), and reduced clinic visits (62.5%). Refusals were attributed to poor knowledge (55.67%), partner/family disapproval (41.33%), preference for another method (35.33%), and fear of complications (33.67%). Most participants were 26–30 years (36.5%), multiparous (66%), graduates (48.5%), from rural areas (62%), and upper middle class (32.7%). Vaginal delivery accounted for 67.5% of insertions. The expulsion rate was 6.84%, with no significant association with type of insertion (p=0.24). At follow-up, 76.31% reported no complaints. Removal rate was 1.58%. Continuation was 91.58% and efficacy 100%, with no failures recorded. Conclusion: PPIUCD is a safe, effective, and highly acceptable contraceptive option with excellent continuation and satisfaction rates. It is particularly advantageous in rural settings where access to follow-up and contraceptive services is limited.